Be Sweet to Babies During Painful Procedures: A Pilot Evaluation of a Parent-Targeted Video. (October 2017) - Harrison, Denise; Larocque, Catherine; Reszel, Jessica; Harrold, JoAnn; Aubertin, Cheryl
Abstract : Background: Breastfeeding (BF), skin-to-skin care (SSC), and sucrose effectively reduce babies' pain during newborn blood work, but these strategies are infrequently used. Our team developed a parent-targeted video intervention showing the effectiveness of the 3 pain management strategies. Purpose: To evaluate neonatal intensive care unit (NICU) parents' (1) baseline knowledge and previous use of BF, SSC, and sucrose for procedural pain management; (2) intention to advocate/use BF, SSC, or sucrose for their infants' future blood work after viewing the video; (3) intention to recommend the video to other parents; and (4) perceptions of the video and identify areas for improvement. Methods: Cross-sectional survey of parents in an NICU. Results: Fifty parents were enrolled: 33 mothers and 17 fathers. More than two-thirds (68%) of parents had prior knowledge of analgesic effects of sucrose; knowledge of SSC and BF as pain-reduction strategies was lower: 44% and 34%, respectively. Eighty-six percent of parents felt the video was the right length; 7 (14%) felt the video was too long. After viewing the video, 96% of parents intended to advocate for BF, SSC, or sucrose for pain management and 88% parents would recommend the video to other parents. Implications for practice: The video is acceptable to parents, is feasible to deliver to parents in an NICU, and has potential to increase parents' intent to advocate for pain management strategies for their infants. Implications for research: Future studies are required to evaluate the effectiveness of this parent-targeted intervention on increasing actual use of pain management in clinical practice. Abstract : Supplemental Digital Content is Available in the Text.